Light-shading and low-expansion-coefficient glass slurry as well as preparation method and application thereof

By coating the surface of aerogel composite materials with a light-shielding, low-expansion-coefficient glass slurry to form a dense ceramic layer, the problems of easy powder shedding and high thermal conductivity of aerogel composite materials under high temperature conditions are solved, thus improving the high-temperature protection and thermal insulation performance of the materials.

CN121225879APending Publication Date: 2025-12-30CHANGSHA RONGLAN MACHINERY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511477649.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-16
Publication Date
2025-12-30

AI Technical Summary

Technical Problem

Existing aerogel composite materials are prone to powdering under high temperature conditions, have high thermal conductivity, and exhibit uneven dispersion of opacifiers in fiber felts.

Method used

A light-shielding, low-expansion-coefficient glass slurry is used. By mixing light-shielding agent powder, glass powder and organic carrier to form a uniform glass slurry, it is coated on the surface of aerogel composite material and then sintered to form a dense ceramic layer, which reduces the coefficient of thermal expansion and improves thermal insulation performance.

Benefits of technology

It effectively prevents powder shedding from the aerogel surface, reduces high-temperature thermal conductivity, improves thermal insulation performance, and the process is simple and controllable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121225879A_ABST
    Figure CN121225879A_ABST
Patent Text Reader

Abstract

The invention discloses light-shading low-expansion-coefficient glass paste and a preparation method and application thereof, and belongs to the technical field of heat insulation composite materials, and the light-shading low-expansion-coefficient glass paste comprises the following components in percentage by mass: 5-30% of light-screening agent powder, 1-40% of glass powder, 30-70% of organic carrier and 0-3% of assistant. The surface of an aerogel composite material is uniformly coated with the slurry, a ceramic layer formed after sintering can improve the heat insulation performance of the aerogel composite material in a high-temperature environment, the surface of a base material can be effectively protected against corrosion damage, and powder falling of the aerogel material is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of thermal insulation composite materials, and particularly relates to a light-shielding and low-expansion-coefficient glass paste as well as a preparation method and application thereof. BACKGROUND

[0002] Generally, an aircraft needs to face high temperature, vibration and other environmental tests in operation. Aerogel composite materials have a three-dimensional network skeleton and a nano-scale porous structure, and are widely used in the thermal insulation layer of an aircraft.

[0003] At present, the most commonly used aerogel composite materials include silica and alumina aerogel materials. Since the overall brittleness of the aerogel is large, the skeleton is prone to fracture under external force, which causes the surface to be prone to powdering. Preparing an enamel layer on the surface of the aerogel to prevent the surface from powdering is a way, but the expansion coefficient of the enamel layer and the substrate needs to be well matched, and the enamel layer cannot crack under sudden cooling and heating.

[0004] Due to high porosity, the aerogel greatly inhibits solid-phase and gas-phase heat conduction, but as the temperature rises, thermal radiation becomes the main way of heat transfer. The introduction of a light-shielding agent can effectively reduce the thermal conductivity under high-temperature thermal radiation and thus improve the thermal insulation performance. At present, the aerogel composite material doped with the light-shielding agent is usually in the form of powder and is doped into the prepared silica sol at the sol-gel stage. The light-shielding agent powder is uniformly dispersed in the fiber felt together with the gel liquid.

[0005] The glass paste is an important electronic material, mainly used for manufacturing thick film elements, and has a wide range of uses in the electronic industry, but the glass paste has not been applied to aerogel thermal insulation materials. SUMMARY

[0006] In view of the problems of the alumina aerogel and the silica aerogel in the prior art, such as easy powdering and high radiation heat conduction under high-temperature conditions, the application provides a light-shielding and low-expansion-coefficient glass paste as well as a preparation method and application thereof. The glass paste doped with the light-shielding agent obtained by the method has a low thermal expansion coefficient after sintering, forms a dense ceramic panel on the surface of the aerogel substrate after sintering, can prevent the aerogel surface from powdering and slagging, can effectively reduce the thermal conductivity of the aerogel under high-temperature conditions, and has a simple and controllable process.

[0007] The technical scheme of the application is as follows: The light-shielding, low-expansion coefficient glass paste provided by the application comprises the following components in percentage by mass: light-shielding agent powder 5-30%, glass powder 10-50%, organic carrier 30-70%, and auxiliary agent 0.1-3%. The paste is uniformly coated on the surface of aerogel composite material, and the ceramic layer formed after sintering can improve the heat insulation performance of the aerogel composite material in a high-temperature environment, effectively protect the surface of the substrate from corrosion and damage, and prevent the aerogel material from falling off.

[0008] The object of the application is achieved by the following technical solutions. The application provides a preparation method of light-shielding, low-expansion coefficient glass paste, which comprises the following steps: S1, ethyl cellulose and solvent are mixed in a mass ratio of 4-15% of ethyl cellulose, 45-60% of pine oil alcohol, 15-25% of alcohol ester twelve, 5-15% of butyl carbitol acetate, and 5-15% of butyl carbitol, and constant temperature stirring is performed at 80-95 DEG C to obtain an organic carrier. S2, light-shielding agent powder 5-30%, glass powder 10-50%, organic carrier 30-70%, and auxiliary agent 0.1-3% are mixed and stirred in a mass ratio, and rolling is performed to less than 15 mu m to obtain glass paste doped with light-shielding agent, which is a light-shielding, low-expansion coefficient glass paste. -6 / K~6.0×10 -6 / K, and is well combined with the surface of aerogel. The light-shielding agent powder is selected from one or more of titanium dioxide, iron oxide, zinc oxide, silicon carbide, zirconium oxide, and carbon black inorganic powder, and the mixing ratio is arbitrary.

[0009] Further, in S1, constant temperature stirring is performed at 80-95 DEG C for 1-5 hours, and the stirring speed is 20 rpm-1000 rpm. Further, constant temperature stirring is performed at 90 DEG C for 3 hours, and the stirring speed is 200 rpm.

[0010] Further, the particle size of the light-shielding agent powder in S2 is 1-5 mu m.

[0011] Further, the glass powder in S2 comprises the following materials in parts by weight: Silicon dioxide 30-80%, Aluminum oxide 10-30%, Boron oxide 5-15%, Calcium oxide 2-15%, Strontium oxide 0.5-5%, Zinc oxide 0.1%~10%; The average particle size of the glass powder is 1.0um~2.5um.

[0012] Further, the auxiliary agent in S2 is a dispersant or a rheological auxiliary agent, the dispersant is a surfactant, and the rheological auxiliary agent is a conventional thickening and thixotropic agent. Specifically, the dispersant is one or more of stearic acid, oleic acid, benzotriazole and derivatives thereof, and the mixing ratio is arbitrary; the rheological auxiliary agent is one or more of polyurethane, acrylic resin, polyurea and derivatives thereof, and the mixing ratio is arbitrary.

[0013] Further, the rolling to below 15um in S2 is performed by using a three-roll machine.

[0014] The application also relates to a light-shielding and low-expansion coefficient glass paste obtained according to the preparation method of the light-shielding and low-expansion coefficient glass paste, the particle size of the glass paste is less than or equal to 15um, the viscosity is 35 Pa·S~100 Pa·S, and the thermal expansion coefficient after sintering is 4.0*10 -6 / K~6.0*10 -6 / K, and the glass paste is well combined with the surface of aerogel.

[0015] The application also relates to the application of the light-shielding and low-expansion coefficient glass paste, the light-shielding and low-expansion coefficient glass paste is coated on the aerogel composite material, and the coating mode includes but is not limited to brushing, spraying, spinning and silk screen printing, and the paste is sintered at 600℃~1000℃.

[0016] Specifically, the application of the light-shielding and low-expansion coefficient glass paste includes the following steps: (1) uniformly coating the glass paste doped with a light-shielding agent on the surface of the aerogel base material, the surface coating thickness is controlled to be 5um~100um, and the aerogel material coated with the paste is obtained; (2) sintering the aerogel material coated with the paste at high temperature, the sintering temperature is 600℃~1000℃, the time is 1h~2h, a dense enamel layer is formed on the surface, the surface of the enamel layer is smooth, and the enamel layer is not peeled off and cracked after being treated at 600℃.

[0017] Further, the coating mode in the step (1) includes but is not limited to brushing, spraying, spinning and silk screen printing, the surface coating thickness is controlled to be 5um~100um, preferably 10um~30um, the thin thickness is difficult to realize uniform control of the coating thickness at present, and the high thickness leads to high overall density of the material and rising thermal conductivity.

[0018] Further, the high-temperature sintering of step (2) preferably has a sintering temperature of 800-1000 DEG C and a time of 1-2 hours.

[0019] Compared with the prior art, the present application has the following beneficial effects: 1. The light-shielding and low-expansion coefficient glass paste of the present application is prepared by uniformly mixing light-shielding agent powder, low-thermal-expansion coefficient glass powder and an organic carrier, and has a low thermal expansion coefficient, which is comparable to that of alumina and silica aerogel composite material. The paste is well combined with the surface of the aerogel composite material substrate after sintering, has a smooth surface, does not crack or peel off after cold and hot impact, and can effectively prevent powder from falling off the surface of the substrate.

[0020] 2. The application of the light-shielding and low-expansion coefficient glass paste of the present application is to uniformly mix light-shielding agent powder, low-thermal-expansion coefficient glass powder and an organic carrier to prepare a glass paste, which can be uniformly coated on the surface of an aerogel substrate and has a controllable coating thickness. The paste forms a dense thin glass-light-shielding agent coating on the aerogel composite material substrate after sintering, which can effectively reduce the high-temperature thermal conductivity of the thermal insulation material. BRIEF DESCRIPTION OF DRAWINGS

[0021] The accompanying drawings are included to provide a further understanding of the present application, and constitute a part of the specification, illustrate the present application and explain the technical scheme of the present application, and do not constitute a limitation on the present application.

[0022] Figure 1 The process flow chart of the preparation method of the light-shielding and low-expansion coefficient glass paste of the present application is shown in the figure. Figure 2 The appearance morphology photo of the aerogel composite material coated with the light-shielding and low-expansion coefficient glass paste prepared in Example 1 of the present application is shown in the figure. Figure 3 The appearance morphology photo of the aerogel composite material coated with the glass paste prepared in Comparative Example 1 of the present application is shown in the figure. Figure 4 The appearance morphology photo of the aerogel composite material coated with the glass paste prepared in Comparative Example 3 of the present application is shown in the figure. DETAILED DESCRIPTION

[0023] The technical scheme in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, but not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0024] Example 1: A method for preparing a light-shielding glass paste with a low coefficient of thermal expansion, such as... Figure 1 As shown, it includes the following steps: S1. Preparation of organic carriers: S1-1. Weigh accurately the following components by weight: 8% ethyl cellulose, 60% terpineol, 15% dodecyl alcohol ester, 10% butyl carbitol acetate, and 7% butyl carbitol, and place them into a round-bottom flask. S1-2. Dissolve the fluid by stirring at a constant temperature of 90℃ for 3 hours at a stirring speed of 200 rpm to obtain a clear and transparent fluid. S2. Preparation of glass slurry: Accurately weigh 19% titanium dioxide (TiO2) with a particle size of 1μm to 3μm, 50% glass powder, 30.5% carrier, and 0.5% additives according to the weight composition. Mix them evenly and then pass them through a three-roll mill to grind them until the fineness is controlled below 12μm and the viscosity is 58 Pa·S.

[0025] The glass powder in this embodiment is composed of 61% silicon dioxide (SiO2), 18.5% aluminum oxide (Al2O3), 9% boron oxide (B2O3), 7.5% calcium oxide (CaO), 1.5% strontium oxide (SrO), and 1.5% zinc oxide (ZnO); the additive is an acrylic resin dispersant.

[0026] The prepared glass slurry was coated onto the surface of a semi-rigid silica aerogel composite material with mullite fiber as the reinforcing phase, dried at 150℃ for 30 min, and then sintered in a muffle furnace at 950℃ for 1 h. The temperature was raised and lowered with the furnace, and the heating rate of the muffle furnace was 10℃ / min. The sintered glaze layer had a thickness of 30 μm.

[0027] Figure 2 This is a photograph showing the morphology of an aerogel composite material coated with a light-shielding, low-expansion-coefficient glass slurry coating prepared in Example 1. After coating, the prepared glass-coated aerogel insulation material exhibits a smooth surface and a coefficient of thermal expansion of 5.0 × 10⁻⁶ from room temperature to 650°C. -6 / K, it does not peel or crack after being heated to 600℃.

[0028] Example 2: A method for preparing a light-shielding, low-expansion-coefficient glass paste includes the following steps: S1. Preparation of organic carriers: S1-1. Weigh accurately the following components by weight: 8% ethyl cellulose, 60% terpineol, 15% dodecyl alcohol ester, 10% butyl carbitol acetate, and 7% butyl carbitol, and place them into a round-bottom flask. S1-2. Dissolve the fluid by stirring at a constant temperature of 95℃ for 3 hours at a stirring speed of 1000 rpm to obtain a clear and transparent fluid. S2. Preparation of glass slurry: Accurately weigh 19% silicon carbide (SiC) with a particle size of 1μm to 2μm, 50% glass powder, 30.5% carrier, and 0.5% additives according to the weight composition. Mix them evenly and then pass them through a three-roll mill to grind them until the fineness is controlled below 12μm and the viscosity is 100 Pa·S.

[0029] The glass powder in this embodiment is composed of 61% silicon dioxide (SiO2), 18.5% aluminum oxide (Al2O3), 9% boron oxide (B2O3), 7.5% calcium oxide (CaO), 1.5% strontium oxide (SrO), and 1.5% zinc oxide (ZnO); the additive is an acrylic resin dispersant.

[0030] The prepared glass slurry was coated onto the surface of a semi-rigid silica aerogel composite material reinforced with mullite fibers. It was dried at 150℃ for 30 min, then sintered in a muffle furnace at 1000℃ for 1 h, with temperature fluctuations throughout the furnace at a rate of 10℃ / min. The sintered glaze layer had a thickness of 30 μm. The prepared glass-coated aerogel insulation material had a smooth surface and a coefficient of thermal expansion of 4.5 × 10⁻⁶ from room temperature to 650℃. -6 / K, it does not peel or crack after being heated to 600℃.

[0031] Example 3: A method for preparing a light-shielding, low-expansion-coefficient glass paste includes the following steps: S1. Preparation of organic carriers: S1-1. Weigh accurately the following components by weight: 8% ethyl cellulose, 60% terpineol, 15% dodecyl alcohol ester, 10% butyl carbitol acetate, and 7% butyl carbitol, and place them into a round-bottom flask. S1-2, Dissolve at a constant temperature of 90℃ with stirring for 3 hours at a stirring speed of 800 rpm. A clear and transparent fluid is obtained. S2. Preparation of glass slurry: Accurately weigh 19% titanium dioxide (TiO2) with a particle size of 5μm to 10μm, 50% glass powder, 30.5% carrier, and 0.5% additives according to the weight composition. Mix them evenly and then pass them through a three-roll mill to grind them until the fineness is controlled below 12μm and the viscosity is 47 Pa·S.

[0032] The glass powder in this embodiment is composed of 61% silicon dioxide (SiO2), 18.5% aluminum oxide (Al2O3), 9% boron oxide (B2O3), 7.5% calcium oxide (CaO), 1.5% strontium oxide (SrO), and 1.5% zinc oxide (ZnO); the additive is an acrylic resin dispersant.

[0033] The prepared glass slurry was coated onto the surface of a semi-rigid silica aerogel composite material reinforced with mullite fibers. It was dried at 150℃ for 30 min, then sintered in a muffle furnace at 800℃ for 2 h with fluctuating furnace temperature at a rate of 10℃ / min. The sintered glaze layer had a thickness of 30 μm. The prepared glass-coated aerogel insulation material had a smooth surface and a coefficient of thermal expansion of 5.5 × 10⁻⁶ from room temperature to 650℃. -6 / K, it does not peel or crack after being heated to 600℃.

[0034] Example 4: A method for preparing a light-shielding, low-expansion-coefficient glass paste includes the following steps: S1. Preparation of organic carriers: S1-1. Weigh accurately the following components by weight: 15% ethyl cellulose, 55% terpineol, 20% dodecyl alcohol ester, 5% butyl carbitol acetate, and 5% butyl carbitol, and place them into a round-bottom flask. S1-2. Dissolve the fluid by stirring at a constant temperature of 80℃ for 5 hours at a stirring speed of 500 rpm to obtain a clear and transparent fluid. S2. Preparation of glass slurry: Accurately weigh 30% titanium dioxide (TiO2) with a particle size of 1μm to 3μm, 39% glass powder, 30.5% carrier, and 0.5% additives according to the weight composition. Mix them evenly and then pass them through a three-roll mill to grind them until the fineness is controlled below 12μm and the viscosity is 55Pa·S.

[0035] The glass powder in this embodiment is composed of 61% silicon dioxide (SiO2), 18.5% aluminum oxide (Al2O3), 9% boron oxide (B2O3), 7.5% calcium oxide (CaO), 1.5% strontium oxide (SrO), and 1.5% zinc oxide (ZnO); the additive is an acrylic resin dispersant.

[0036] The prepared glass slurry was coated onto the surface of a semi-rigid silica aerogel composite material reinforced with mullite fibers. It was dried at 150℃ for 30 min, then sintered in a muffle furnace at 950℃ for 1.5 h, with temperature fluctuations during furnace operation at a rate of 10℃ / min. The sintered glaze layer had a thickness of 30 μm. The prepared glass-coated aerogel insulation material had a smooth surface and a coefficient of thermal expansion of 6.0 × 10⁻⁶ from room temperature to 650℃. -6 / K, it does not peel or crack after being heated to 600℃.

[0037] Example 5: The application of a light-shielding, low-expansion-coefficient glass paste includes the following steps: S1. Preparation of organic carriers: S1-1. Weigh accurately the following components by weight: 4% ethyl cellulose, 45% terpineol, 25% dodecyl alcohol ester, 15% butyl carbitol acetate, and 11% butyl carbitol, and place them into a round-bottom flask. S1-2. Dissolve the fluid by stirring at a constant temperature of 85℃ for 4 hours at a stirring speed of 100 rpm to obtain a clear and transparent fluid. S2. Preparation of glass slurry: Accurately weigh 5% titanium dioxide (TiO2) with a particle size of 1μm to 3μm, 50% glass powder, 44.5% carrier, and 0.5% additives according to the weight composition. Mix them evenly and then pass them through a three-roll mill to grind them until the fineness is controlled below 12μm and the viscosity is 35Pa·S.

[0038] The glass powder in this embodiment is composed of 61% silicon dioxide (SiO2), 18.5% aluminum oxide (Al2O3), 9% boron oxide (B2O3), 7.5% calcium oxide (CaO), 1.5% strontium oxide (SrO), and 1.5% zinc oxide (ZnO); the additive is an acrylic resin dispersant.

[0039] The prepared glass slurry was coated onto the surface of a semi-rigid silica aerogel composite material reinforced with mullite fibers. It was dried at 150℃ for 30 min, then sintered in a muffle furnace at 900℃ for 2 h with fluctuating furnace temperature at a rate of 10℃ / min. The sintered glaze layer had a thickness of 30 μm. The prepared glass-coated aerogel insulation material had a smooth surface and a coefficient of thermal expansion of 4.0 × 10⁻⁶ from room temperature to 650℃. -6 / K, it does not peel or crack after being heated to 600℃.

[0040] Comparative Example 1: The difference between Comparative Example 1 and Example 2 lies in the change of glass powder and carrier content. Specifically, the glass powder content is adjusted to 5%, and the carrier content is adjusted to 75.5%, while the rest is the same as in Example 1.

[0041] Figure 3 The image shows the appearance of the aerogel composite material coated with glass slurry prepared in Comparative Example 1. It can be seen that reducing the amount of glass powder will cause the coating to crack and shed powder.

[0042] Comparative Example 2: The difference between Comparative Example 2 and Example 2 lies in the changes in the content of the opaque agent and the carrier. Specifically, the content of the opaque agent is adjusted to 1%, and the content of the carrier is adjusted to 48.5%. The rest is the same as in Example 1.

[0043] Comparative Example 3: The difference between Comparative Example 3 and Example 2 lies in the changes in the content of opaque agent and glass powder. Specifically, the content of opaque agent is adjusted to 35%, and the content of glass powder is adjusted to 34%. The rest is the same as in Example 1.

[0044] Figure 4 The image shows the appearance of the aerogel composite material coated with glass slurry prepared in Comparative Example 3. It can be seen that when the content of opacifier powder in the slurry is too high, the coefficient of expansion of the coating does not match that of the substrate, and cracking will occur during the heat treatment process.

[0045] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that no coating was applied; specifically, the silica aerogel composite material with mullite fiber as the reinforcing phase was tested directly.

[0046] Results and Discussion: The aerogel composite materials coated with glass slurry prepared in Examples 1, 2, 3, 4, 5, Comparative Examples 1, 2, 3, and 4 have the following properties:

[0047] The results show that: 1. This invention uses glass powder to prepare a slurry, which is then coated and sintered to combine the glass slurry with an alumina / silica system aerogel thermal insulation material. The coating has an expansion coefficient close to that of the aerogel substrate, and the prepared coating has a good surface condition without delamination or cracking, which can effectively improve the powder shedding of aerogel materials.

[0048] 2. The test results of Examples 1-5 show that the type and content of the opaque agent will affect the thermal conductivity of the insulation material. Increasing the content of the opaque agent and increasing the number of coating layers under the same thickness will result in a lower high-temperature thermal conductivity of the insulation material. Adjusting the content of the carrier can adjust the viscosity of the slurry.

[0049] 3. The appearance morphology photographs of the aerogel composite material coated with glass slurry prepared in Comparative Example 1 show that reducing the amount of glass powder will cause the coating to crack and shed powder.

[0050] 4. The test results of Comparative Example 2 show that when the content of the opaque agent is low to a certain level, the opaque agent has almost no effect on the heat insulation effect of the heat insulation material. This also indicates that introducing a certain amount of opaque agent components into the glass paste can improve the heat insulation effect of the heat insulation material.

[0051] 5. The appearance morphology photographs of the aerogel composite material coated with glass slurry prepared in Comparative Example 3 show that when the proportion of opaque agent in Comparative Example 3 is further increased, the coefficient of thermal expansion of the coating does not match that of the substrate when the content of opaque agent powder in the slurry is too high, and cracking will occur during the heat treatment process.

[0052] 6. The test results of Comparative Example 4 show that the aerogel substrate alone has surface powder shedding.

[0053] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing a solar control, low coefficient of expansion glass paste, characterized in that, It comprises the following steps: S1, ethyl cellulose and solvent are mixed according to the mass ratio of 4%-15% ethyl cellulose, 45%-60% terpineol, 15%-25% alcohol ester twelve, 5%-15% butyl carbitol acetate and 5%-15% butyl carbitol, constant temperature stirring at 80-95 DEG C, dissolving to obtain an organic carrier; S2, according to the mass ratio, the sunscreen powder 5%~30%, glass powder 10%~50%, organic carrier 30%~70%, auxiliary 0.1%~3% are mixed and stirred uniformly, and are rolled to 15um or less, to obtain a sunscreen doped glass paste, which is a sunscreen, low expansion coefficient glass paste, the particle size of the glass paste is ≤15um, the viscosity is 35 Pa·S~100 Pa·S, and the thermal expansion coefficient after sintering is 4.0×10 -6 / K~6.0×10 -6 / K, which is well combined with the aerogel surface; The opacifying agent powder is selected from one or more of titanium dioxide, iron oxide, zinc oxide, silicon carbide, zirconium oxide and carbon black inorganic powder, and the mixing ratio is arbitrary.

2. The method of claim 1, wherein the low-expansion glass paste is prepared by the steps of: preparing a first paste by mixing a first glass frit with a first solvent; preparing a second paste by mixing a second glass frit with a second solvent; and mixing the first paste and the second paste. In S1, constant temperature stirring is carried out at 80-95 DEG C for 1-5 hours, and the stirring speed is 20 rpm-1000 rpm.

3. The method of claim 2, wherein the glass frit is a low-expansion, light- absorbing glass frit. In S1, constant temperature stirring is carried out at 90 DEG C for 3 hours, and the stirring speed is 200 rpm.

4. The method of claim 1, wherein the low-expansion glass paste is prepared by the steps of: preparing a glass frit by mixing and melting a raw material of the glass paste; and pulverizing the glass frit. The particle size range of the opacifying agent powder in S2 is 1-5 μm.

5. The method for preparing a light-shielding, low-expansion-coefficient glass slurry according to claim 1, characterized in that, The glass powder in S2 comprises the following materials by weight: Silicon dioxide 30%-80%, Aluminum oxide 10%-30%, Boron oxide 5%-15%, Calcium oxide 2%-15%, Strontium oxide 0.5%-5%, Zinc oxide 0.1%-10%; The average particle size of the glass powder is 1.0-2.5 μm.

6. The method for preparing a light-shielding, low-expansion-coefficient glass slurry according to claim 1, characterized in that, The auxiliary agent in S2 is a dispersant or a rheological auxiliary agent, the dispersant is a surfactant, and the rheological auxiliary agent is a conventional thickening and thixotropic agent.

7. A method of making a solar control, low coefficient of expansion glass paste according to claim 6, wherein, The dispersant is one or more of stearic acid, oleic acid, benzotriazole and its derivatives, and the mixing ratio is arbitrary; the rheological auxiliary agent is one or more of polyurethane, acrylic resin and polyurea and its derivatives, and the mixing ratio is arbitrary.

8. A solar control, low coefficient of expansion glass paste, characterized in that, The preparation method of the light-shielding, low-expansion coefficient glass paste according to any one of claims 1-7 is characterized in that the particle size of the glass paste is ≤15 μm, the viscosity is 35 Pa·S~100 Pa·S, the sintering coefficient of thermal expansion is 4.0×10 -6 / K~6.0×10 -6 / K, and is well combined with the aerogel surface.

9. Use of a solar control, low coefficient of expansion glass frit as claimed in claim 8, characterized in that, It comprises the following steps: (1) The opacifying agent doped glass paste is uniformly coated on the surface of the aerogel substrate, the surface coating thickness is controlled to be 5-100 μm, and the aerogel material coated with the paste is obtained; (2) The obtained aerogel material coated with the paste is sintered at high temperature, the sintering temperature is 600-1000 DEG C, the time is 1-2 hours, a dense enamel layer is formed on the surface, the surface of the enamel layer is smooth, and the enamel layer does not peel off and crack after 600 DEG C high temperature treatment.

10. Use of a solar control, low coefficient of expansion glass paste according to claim 9, characterized in that, In step (1), the coating method includes but is not limited to brushing, spraying, spinning and screen printing, and the surface coating thickness is controlled to be 5-100 μm.